PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN METODE PREVIEW, QUESTION, READ, REFLECT, RECITE, AND REVIEW (PQ4R) DI KELAS IV SD - Irayani, Wittin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This class action research aimed at describing improve skills of reading understanding by using the learning methods of Preview, Question, Read, Reflect, Recite, and Review (PQ4R). The subject of this research is teacher and learners of grade four elementary school 16 Balimbing. The approach used is a qualitative and quantitative. The result showed theaverage of student learning outcome on the first cycle was 73 for before reading, 51 for reading, and 55 for after reading,but on the second cycle, its average increased to 86, 70, and 75 respectively. Kata kunci: membaca pemahaman; metode preview, question, read, reflect, recite, and review (PQ4R)